2003
DOI: 10.1115/1.1530627
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of the 200-kWth HiTRec-II Open Volumetric Air Receiver

Abstract: The High Temperature Receiver (HitTRec) consists of a modular ceramic absorber, a supporting structure and an air-return system. It has been designed to prevent possible flow instability at 700-800°C average outlet air temperature with atmospheric pressure. The HiTRec-II prototype was developed to solve the structural problems of the first prototype (HiTRec-I). Testing in the Plataforma Solar de Almerı´a (PSA) test bed lasted from November 2000 through May 2001, accumulating 150 test hours under concentrated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(65 citation statements)
references
References 10 publications
1
62
0
2
Order By: Relevance
“…One operational strategy is to control the flow rate of the heat transfer fluid, such that POM is stabilized. Using POM facilitates the effective comparison of various receivers operating in different environments [16,19].…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
“…One operational strategy is to control the flow rate of the heat transfer fluid, such that POM is stabilized. Using POM facilitates the effective comparison of various receivers operating in different environments [16,19].…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
“…Moreover, experiments have demonstrated that even partial heating of this receiver will allow achieving volumetric heating. The porosity of the designed receiver is 52% that compares well with Solair 200 [16]. Such receivers are usually made of material with high thermal conductivity, like, Silicon-carbide (~100-300 W/mK) in temperature range from 200-600ᵒC [17,18,19].…”
Section: Open Volumetric Air Receivermentioning
confidence: 97%
“…Heating up of the air would advantageously start at the highly irradiated and exposed front before flowing through a serpentine path towards the 'shielded' back. The combination of the temperature increase towards the inside of the receiver and the increased convective heat transfer surface compared to the receiver aperture area is commonly referred to as the 'volumetric effect' [8].…”
Section: The Hpar Conceptmentioning
confidence: 99%